Analysis of the Impact of Organizational Structure and Bureaucratic Governance on the Workload of SCA Employees at the Secretariat of the Surabaya City RPRA.Analysis of the Impact of Organizational Structure and Bureaucratic Governance on the Workload of SCA Employees at the Secretariat of the Surabaya City RPRA. - Agus Sunarto; Amirul Mustofa (Pt. Anagata Sembagi Education, 2025)
This study aims to analyze the impact of organizational structure and bureaucratic governance on the workload of State Civil Apparatus (SCA) employees at the Secretariat of the Surabaya City RPRA. The workload of SCA employees is a major challenge in maintaining productivity and work balance, especially within a hierarchical organizational structure and suboptimal bureaucratic governance. The implementation of Surabaya Mayor Regulation Number 68 of 2021 has simplified the organizational structure at the RPRA Secretariat from four to three sections: the General Section, the Meeting and Legislation Section, and the Information and Protocol Section. This change has the potential to create workload imbalances and affect employee performance. This study employs a descriptive method with a qualitative approach through observations and document analysis. The results indicate that an overly hierarchical organizational structure slows down coordination and task distribution, while inefficient bureaucratic governance burdens employees with repetitive administrative procedures. The proposed recommendations include organizational restructuring, employee capacity development, and the implementation of digital technology to streamline administrative processes. Bureaucratic reforms focused on efficiency and effectiveness are expected to better manage the workload of SCA employees, create a conducive work environment, enhance productivity, and support the achievement of optimal organizational goals.